Implementasi Metode Tasmi’ Dan Takrir Dalam Meningkatkan Kualitas Hafalan Al-Qur’an Santri - Doni Saputra (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
Tasmi' method is the activity of listening to the recitation of our Qur'an to others, tasmi activities' are usually carried out regular pesantren also among NU citizens who do it. While the takrir method is a method used to repeat memorization that has been memorized as well as has been deposited to the teacher or bunyai, this method aims so that memorization that has been memorized remains stored in brain memory so that it will not be easily forgotten. The type of research used in this study is descriptive qualitative research. The process of data analysis as well as qualitative research, then used data analysis techniques with data reduction, data presentation, and verification. The implementation of the tasmi' and takrir methods in improving the quality of santri memorization shows the results that the application of the method can run well and get satisfactory results. The process of data analysis as well as qualitative research, then used data analysis techniques with data reduction, data presentation, and verification. The implementation of the tasmi' and takrir methods in improving the quality of santri memorization shows the results that the application of the method can run well and get satisfactory results. The results showed that at the time of implementation of the method of memorizing the Qur'an using the tasmi' method and takrir can improve the quality of memorization santri. It can be seen the improvement by the way of completion in memorization, the difference between the initial method before use and after use, increasing motivation and interest in santri, santri is very enthusiastic and produces the quality memorization of bittartil and bittajwid smoothly and on target, In addition, it can be seen from the majority of santri that they can achieve according to the predetermined target which from the beginning 60% who reached their memorization according to the target now become approximately 80% can achieve the target as determined by Pondok Pesantren Tahfidzil Qur'an Lilbanat Sumbersari Kediri.